Torque Measures of Common Therapies for the Treatment of Loss of Knee Flexion - Uhl, Timothy L. (SAGE Publications, 2012)
BACKGROUND: Conservative treatment protocols to effectively treat knee flexion motion restrictions are dependent in part on the torque applied to the joint. HYPOTHESES: Clinicians apply greater torque with the test leg in a simulated prone position than in a seated position. Clinicians also apply greater torque than a dynamic splint or a static progressive stretch brace. Finally, clinicians apply a torque equal to the high-intensity stretch device. STUDY DESIGN: bservational study. METHODS: An instrumented test leg was used to record peak torque applied by 14 licensed clinicians (7 women, 7 men; age, 44.3 ± 10.2 years; height, 172.9 ± 13.2 cm; weight, 72.6 ± 13.0 kg) during knee flexion mobilizations and 3 types of mechanical therapy (dynamic splint, static progressive stretch, and high-intensity stretch). RESULTS: The dynamic splint applied 5.1 ± 0.1 N·m, while the static progressive stretch brace applied 20.8 ± 2.2 N·m. Clinicians applied 49.5 ± 22.4 N·m with the test leg in a seated position and 55.8 ± 22.0 N·m with the leg in a prone position. The high-intensity stretch device applied up to 214.7 ± 29.2 N·m. All comparisons were statistically significant (P ≤ 0.02) with the exception of the 2 testing positions (P = 0.94). CONCLUSIONS: The results demonstrate that the torques applied to the knee differ between passive stretching therapies. Clinicians should be cognizant of these torque differences when constructing treatment protocols for patients with limited knee flexion range of motion.